Definition and Cycle of Diptera (Texas Journal of Agriculture and Biological Sciences, 2024)
The life cycle of a fly consists of four stages: egg, larva, pupa, and adult. Since larval forms, always morphologically distinct from adults, also occupy different habitats, flies in effect live two distinct lives and thus are able to adapt successfully to environmental changes. In some flies (e.g., robber flies) neither the larval nor the adult stage predominates; the larva feeds actively in soil, and adult flies of both sexes catch other insects in flight. Among mosquitoes, black flies, and related bloodsucking flies, the larvae have characteristic structures and live active lives under water; the complex mating process of the adults is followed (in the case of females) by bloodsucking and egg laying.